2007
DOI: 10.1681/asn.2007020243
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Oligogenic Inheritance in Nephronophthisis

Abstract: Nephronophthisis is a recessive cystic renal disease that leads to end-stage renal failure in the first two decades of life. Twenty-five percent of nephronophthisis cases are caused by large homozygous deletions of NPHP1, but six genes responsible for nephronophthisis have been identified. Because oligogenic inheritance has been described for the related Bardet-Biedl syndrome, we evaluated whether mutations in more than one gene may also be detected in cases of nephronophthisis. Because the nephrocystins 1 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
112
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(117 citation statements)
references
References 25 publications
2
112
2
1
Order By: Relevance
“…reported [11,12]. We also found compound heterozygosity across multiple NPHP genes in some of our Japanese nephronophthisis patients.…”
Section: Discussionsupporting
confidence: 63%
“…reported [11,12]. We also found compound heterozygosity across multiple NPHP genes in some of our Japanese nephronophthisis patients.…”
Section: Discussionsupporting
confidence: 63%
“…The first case was homozygous for an obligatory splice acceptor-site mutation (IVS26 ϩ 1 GϾA), and this child had no extrarenal manifestations of disease. 12 The second case was combined heterozygous for a frameshift mutation (435_438delAAGT) and a splice mutation (IVS24-1GϾC) in NPHP3 13 and was also heterozygous for a frameshift mutation in the NPHP4 gene. This child had liver fibrosis and reached end-stage renal disease at age 3 years.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that NPHP sometimes accompanies simultaneous mutations in different NPHP genes. 21 Although the prevalence of renal abnormalities due to the mutation in other NPHP genes is low, there is a possibility that the difference in eGFR might be caused in part by the interaction between mutations in other NPHP genes.…”
Section: Discussionmentioning
confidence: 99%